Total Glossectomy with Wide Excision Base of Tongue, Margined Mandibulectomy, Both Neck Nodes Resection with ALTFF: A Case Study - Thammakiat, Kanokwan (Royal Thai Air Force Medical Gazette, 2023)
Objective : To study, analyze problems and to develop a nursing practice guideline for tongue cancer patients receiving anesthesia in complicated surgery. patients receiving anesthesia for evaluate nursing performance effectively of tongue cancer and neck lymph node surgery patients with lateral thigh graft by microsurgery Methods: A case study of purposive selection in tongue cancer patients receiving anesthesia during tongue cancer and neck lymph node surgery patients with lateral thigh flap by microsurgery. The study was conducted while nursing during preparation anesthesia visit as given while administering anesthesia and post anesthesia visit. Data was collection from medical records, physical examination, history taking from patients and relatives, problem finding, nursing diagnosis according to use Orem’s self-care theory concept. Nursing practice according to nursing , planning and nursing practice according to nursing diagnoses Summary and evaluation of nursing outcomes. Results: A 49-year-old Thai man was diagnosed with tongue cancer. sent to be treated at Rajavithi Hospital, the diagnosis by computed tomography of the neck A tumor measuring 5.7 x 6.2 x 7.5 cm was found in the middle of the tongue. out on the left side of the tongue has spread to hyoid bone internal oral organs and lymph nodes on both sides The doctor plans the treatment. by doing surgery together with radiotherapy after surgery The nurse anesthetist had a visit to the patient one day before giving anesthesia. The patient had difficulty intubation. Plan airway management with the anesthesiologist. Flexible Fiberoptic Bronchoscope intubation (FOBI) was performed. Total Glossectomy with Wide excision base of tongue, margine mandibulectomy, both neck nodes resection with ALTFF has done. The surgery took 9 hours, and there were no complications during the operation. After the surgery, the patient was transferred to the semi-critical ward for otolaryngology and breathing control. Trace the transplanted tissue, good redness, not pale, without abnormal complications. Make sure the patient is facing right at 30º to prevent strain on the newly connected vein, visit after anesthesia There were no complications after receiving anesthesia. On the 4th day postoperatively, there was an infection from the surgical wound due to a hole in the mouth. Enter the operating room for surgery. Explore neck with resuture to. No postoperative fever was found. Patients were consulted by nutrition therapists. Physical therapists and occupational therapists, including a period of hospitalization of 1 month and 1 day, can be discharged Conclusion: Nursing care of tongue cancer patients undergoing surgery with lateral thigh free flap. By histological method Nursing and anesthesia Standardized nursing procedures must be used from pre-operative, intra operation, and post-operative stages with efficiency. Therefore, it can prevent complications that may occur with patients.